Pulmonary mucormycosis in immunocompetent hosts diagnosed by bronchioalveolar lavage. Issue 4 (12th April 2021) - Kumar, Sunil; Joshi, Divya
Abstract : Mucormycosis is a rare infection caused by Mucorales fungi belonging to Zygomycetes class. It can present with spectrum of symptoms and signs based of organ involvement. Common forms of mucormycosis includes rhinocerebral, cutaneous, gastrointestinal, pulmonary, disseminated and miscellaneous forms involving bones, breast, kidney and central nervous system. Pulmonary mucormycosis usually present with fever, cough, haemoptysis and is usually seen in immunocompromised patients like patients with diabetes or leukaemia, or those on chemotherapy or immunosuppressive therapy and rare in immunocompetent patients (6.25% of cases). Pulmonary mucormycosis can be diagnosed by radiological imaging studies, bronchoalveolar lavage (BAL) and histopathological evaluation of biopsy of the lesion; however, the gold standard is a positive fungal culture. Here, we describe two cases of pulmonary mucormycosis diagnosed by BAL in an immunocompetent patient.